Diversity Management - Dickie, Carolyn; Soldan, Zhanna (Tilde Publishing Australia, 2008)
Synopsis: The 'diversity' concept provides an essential means of developing an inclusive, competitive workplace in a comprehensive, encompassing and inter-disciplinary manner. This book is an experiential learning tool for people interested in 21st century business; it can be used both as a resource for research and as a textbook. It has theoretical, conceptual and practical content as well as numerous discussion points and case examples which will challenge current and future business managers.